(untitled) (Literary Voice, 2024)
The research paper observes the play of subjectivity that the novel White Noise by Don DeLillo entails. It depicts the juxtaposition of different identities by the characters to lead a life they desire. In this book, DeLillo explores the dynamics of identity that underpin postmodern civilization. The modern man who believed in wholeness and unity has been replaced by a postmodern man who is in complete contrast, owns a constructed identity and lacks uniqueness. This paper points toward the fragmented self, and search for the true self.